Estudos metabolômicos de compostos orgânicos voláteis (COVs) associados à resistência de clones de cajueiro tipo anão precoce frente ao ataque de diferentes fitopatógenos - Sousa, Debora Bezerra de (2022)
Black mold, anthracnose, and powdery mildew are caused by the phytopathogens Pilgeriella anacardia Arx & Müller, Colletotrichum gloeosporioides and Pseudoidium anacardii (F. Noack) U. Braun & R.T. A. Cook respectively, being the most important fungal diseases that spread easily in cashew orchards (Anacardium occidentale). However, some early dwarf cashew clones show different responses in relation to resistance and susceptibility to the attack of these phytopathogens, with the mechanisms for this behavior not yet been clarified. In this work, the profile of volatile organic compounds (VOCs) emitted by the leaves and cashew nuts of four types of early dwarf cashew clones ('CCP76', 'BRS226', 'BRS189', and 'BRS265') with different levels of resistance and susceptibility to the aforementioned diseases was investigated from March to December 2019 by GC-MS. The results obtained allowed the identification of a total of 116 VOCs from leaves and 40 VOCs from cashew nuts, characterized as terpenes, alcohols, esters, aldehydes, ketones, and hydrocarbons. From these data, the construction of multivariate analysis graphs (HCA, PLS-DA, and OPLS-DA) showed significant differences between the VOCs profile of resistant clones, in relation to those susceptible to phytopathogens. In these analyzes it was possible to verify that compounds such as 3-hexen-1-ol, (Z)-2-hexen-1-ol, (E)-2-hexen-1-ol, 1-hexanol, α-pinene, β- myrcene, methyl salicylate, and α-copaene may contribute to the greater resistance of clones 'BRS226' and 'BRS265' in relation to black mold, while compounds (E)-2-hexenal, (E)-3-hexen-1-ol, α-terpinene, γ-terpinene, β-pinene, observed in clones 'CCP76', 'BRS226' and 'BRS189’, are related to anthracnose resistance. The compounds ethyl isovalerate, ethyl tiglate, ethyl hexanoate, ethyl 3-methyl-pentanoate, α-pinene, β-pinene were identified in cashew nuts as the compounds that possibly contribute to the greater resistance of 'CCP76', 'BRS226', and 'BRS265' clones in relation to powdery mildew. These results corroborate the data in the literature that suggest VOCs as biocontrol agents in phytopathogens prevention.